Magnetic excitations in the topological semimetal YbMnSb2 - Tobin, SM; Soh, J-R; Su, H; Piovano, A; Stunault, A; Rodríguez-Velamazán, JA; Guo, Y; Boothroyd, AT (American Physical Society, 2023)
We report neutron scattering measurements on YbMnSb2 which shed light on the nature of the magnetic moments and their interaction with Dirac fermions. Using half-polarized neutron diffraction we measured the field-induced magnetization distribution in the paramagnetic phase and found that the magnetic moments are well localized on the Mn atoms. Using triple-axis neutron scattering we measured the magnon spectrum throughout the Brillouin zone in the antiferromagnetically ordered phase, and we determined the dominant exchange interactions from linear spin-wave theory. The analysis shows that the interlayer exchange is five times larger than in several related compounds containing Bi instead of Sb. We argue that the coupling between the Mn local magnetic moments and the topological band states is more important in YbMnSb2 than in the Bi compounds.